Evaluation of Groundnut Value Chain in Kebbi State, Nigeria - Aliyu Danmaigoro; Ayuba Gona; T Ishaya; Vanessa Ezekiel Naduku (MultiTech Publisher, 2023)
Data were collected through Semi structured survey questionnaires and Interview of key informants in line with the purpose of the study. Both simple random and purposive sampling method were used to select the respondents from different segments of the entire value chain. Sixty (60) groundnut farmers were randomly selected, thirty (30) wholesalers/retailers (traders) and thirty (30) processors were selected from the four agricultural zones in the State. Thus, given a total of one hundred and twenty (120) as sample size. Data were analysed using Functional Analysis, Descriptive statistics, Marketing margin, Net Farm Income (NFI) Analysis, and Ordinary Least Squares Multiple Regression Analysis. Results revealed that the major groundnut value chain actors are input suppliers, farmers, processors and traders. Their functions include production of groundnut, supply of inputs such as seeds agro-chemicals, processing, distribution and transportation of groundnut. The study revealed that both groundnut Farmers, Processors and Traders realized a profit of (N41, 044, N30, 865 and N39, 000 respectively) however, farmers realized more profit than the processors and traders. The major practices used in groundnut production by the farmers is mixed cropping (60%), sole cropping (23.3%), and both sole and mixed cropping (11.7%), respectively. The determinants of groundnut quantity supplied to the market include, Farming experience (0.335) Ownership of transportation facility (2.834), Distance to market (4.007), Agricultural extension service (3.001), and Quality of groundnut produced (1.899). The major constraints encountered by the groundnut value chain actors include; for groundnut farmers, high cost of inputs supply (53.33%), and inadequate supply of improved variety (31.00%). For processors the constraints are High cost of processing equipment (53.33%), Lack of access to credit (33.34%). While the major constraints encountered by traders are; Insecurity on rural - urban market roads (50.00%) and Fluctuation on the prices of groundnut (30.00%).